(untitled) (Biocenosis, 2025)
Brugmansia × candida (Persoon), belonging to the Solanaceae family and known in Costa Rica as queen of the night, is an evergreen ornamental shrub that can grow up to six meters. In addition to its decorative use, it is commonly planted as a living fence in coffee plantations, pastures, and around houses, displaying showy flowers in white, yellow, or pink hues. This species contains tropane alkaloids - mainly scopolamine, hyoscyamine, and atropine -spread throughout the plant, with the highest concentrations found in the flowers and leaves, making it potentially toxic. The correct botanical identification of this species is essential for the diagnosis and treatment of poisoning cases, which are attended by the National Poison Center of Costa Rica, located in the National Children’s Hospital. Given its toxicity and the attraction its flowers and fragrance exert on children, it is crucial to promote education and precaution in handling this plant to prevent possible poisoning.